2011
DOI: 10.1016/j.trsl.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient plasma levels achieved during treatment that reduces noise-induced hearing loss

Abstract: Hearing loss encompasses both temporary and permanent deficits. If temporary threshold shift (TTS) and permanent threshold shift (PTS) share common pathological mechanisms, then agents that reduce PTS should also reduce TTS. Several antioxidant agents have reduced PTS in rodent models; however, reductions in TTS have been inconsistent. This study first determined whether dietary antioxidants (beta-carotene, and vitamins C and E) delivered in combination with magnesium (Mg) reliably increase plasma concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 118 publications
1
18
0
Order By: Relevance
“…Pre-clinical studies have shown benefit for several molecules that can be obtained from normal healthy diets; some of these agents include beta-carotene, vitamins C and E, and magnesium (Le Prell et al, 2007a; Tamir et al, 2010; Le Prell et al, 2011a; Le Prell et al, 2011b), D-methionine (Campbell et al, 2007; Campbell et al, 2011; Clifford et al, 2011; Claussen et al, 2013; Lo et al, 2013; Rewerska et al, 2013), and N-acetylcysteine (Kopke et al, 2000; Kopke et al, 2005; Bielefeld et al, 2007; Kopke et al, 2007; Clifford et al, 2011). Ultimately, it may indeed be possible to prevent the secondary “spread” of damage that occurs with continued metabolic stress after noise stress.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies have shown benefit for several molecules that can be obtained from normal healthy diets; some of these agents include beta-carotene, vitamins C and E, and magnesium (Le Prell et al, 2007a; Tamir et al, 2010; Le Prell et al, 2011a; Le Prell et al, 2011b), D-methionine (Campbell et al, 2007; Campbell et al, 2011; Clifford et al, 2011; Claussen et al, 2013; Lo et al, 2013; Rewerska et al, 2013), and N-acetylcysteine (Kopke et al, 2000; Kopke et al, 2005; Bielefeld et al, 2007; Kopke et al, 2007; Clifford et al, 2011). Ultimately, it may indeed be possible to prevent the secondary “spread” of damage that occurs with continued metabolic stress after noise stress.…”
Section: Discussionmentioning
confidence: 99%
“…The current study assessed the potential prevention of TTS by a dietary supplement using this laboratory-based music exposure. The selection of the active agents within the dietary supplement was motivated by previous studies in mice and guinea pigs showing pre-noise dosing efficacy for NIHL and TTS prevention with the combination of β-carotene, vitamins C and E, and Mg [Le Prell et al, 2011a, b; Le Prell et al, 2007; Tamir et al, 2010]. …”
Section: Introductionmentioning
confidence: 99%
“…[31] The hearing threshold shift was evaluated 2 min after the end of exposure (TTS 2 ), then after 15 min (TTS 15 ) and 30 min (TTS 30 ). Subsequent measures were taken every 5 min until complete recovery.…”
Section: Methodsmentioning
confidence: 99%
“…[11,12] Magnesium has also been tested, alone or in compounds with other antioxidants (β-carotene, Vitamins E and C) with encouraging results. [13][14][15] Supra-physiological administration of Vitamin B12 appears to be effi cacious in protecting hearing, especially at the frequencies of 3 and 4 kHz. [16] Other studies have shown some effi cacy in preventing NIHL for glutathione precursors, such as N-acetylcysteine and methionine, or other antioxidants like alpha-lipoic acid.…”
Section: Introductionmentioning
confidence: 99%